Analysis And Design Of Two Flyback-based Integrated Converters For The Implementation Of Lfsw Electronic Ballasts - Marchesan, Tiago B.; Costa, Marco Dalla; Perdigão, Marina; Alonso, J. Marcos; Prado, Ricardo N. (Eletrônica de Potência, 2008)
This paper presents a simple configuration, based on the integration of two flyback converters, to supply high intensity discharge (HID) lamps with a low frequency square waveform (LFSW), in order to avoid the occurrence of the acoustic resonance (AR) phenomenon. The proposed topology is compared to a previous presented one. Both topologies integrate two flyback converters in different ways. Losses of both integration modes are compared and advantages are discussed in respect to current and voltage components stress. The proposed electronic ballast presents a high efficiency with a reduced number of components and no over current stress in the shared switch. Experimental results validate both configurations.